Growth of Oxygen Minimum Zones May Indicate Approach of Global Anoxia - Yazeed Alhassan; Sergei Petrovskii (Mathematics)
The dynamics of large-scale components of the Earth climate system (tipping elements), particularly the identification of their possible critical transitions and the proximity to the corresponding tipping points, has been attracting considerable attention recently. In this paper, we focus on one specific tipping element, namely ocean anoxia. It has been shown previously that a sufficiently large, ‘over-critical’ increase in the average water temperature can disrupt oxygen production by phytoplankton photosynthesis, hence crossing the tipping point, which would lead to global anoxia. Here, using a conceptual mathematical model of the plankton–oxygen dynamics, we show that this tipping point of global oxygen depletion is going to be preceded by an additional, second tipping point when the Oxygen Minimum Zones (OMZs) start growing. The OMZ growth can, therefore, be regarded as a spatially explicit early warning signal of the global oxygen catastrophe. Interestingly, there is growing empirical evidence that the OMZs have indeed been growing in different parts of the ocean over the last few decades. Thus, this observed OMZ growth may indicate that the second tipping point has already been crossed, and hence, the first tipping point of global ocean anoxia may now be very close.